2016
DOI: 10.1039/c5ra26176g
|View full text |Cite
|
Sign up to set email alerts
|

Excellent lithium ion storage property of porous MnCo2O4 nanorods

Abstract: The porous MnCo2O4 nanorods have been successfully prepared by a simple and economic method and exhibited a high electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Both peaks could be deconvoluted indicating the presence of Mn 2+ and Mn 3+ . The two sub peaks at ~642.2 and 654.0 eV can be assigned to Mn 2+ , while the other two at ~644.5 and 657.3 eV are attributed to the presence of Mn 3+ 43. Comparison of the integrated areas of the deconvoluted curves indicated that ~39.5% of the manganese present was in the Mn 3+ valence state.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Both peaks could be deconvoluted indicating the presence of Mn 2+ and Mn 3+ . The two sub peaks at ~642.2 and 654.0 eV can be assigned to Mn 2+ , while the other two at ~644.5 and 657.3 eV are attributed to the presence of Mn 3+ 43. Comparison of the integrated areas of the deconvoluted curves indicated that ~39.5% of the manganese present was in the Mn 3+ valence state.…”
Section: Resultsmentioning
confidence: 95%
“…Based on the analysis of the CV curves and previous reports41435158 and the surface stoichiometry suggested from XPS analysis, the Li reactions for Ni-Mn-Co-O IO materials are believed to proceed as follows:…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the materials were obtained by calcination, which will lead to the formation of lattice defects in the typical nanostructure. These lattice defects will provide more active sites for Li + insertion/extraction, which could improve the specific capacity of the materials [50]. On the other hand, the decomposition and reformation of the SEI layer will also lead to the increase in capacity [51], but the central aspect is that the introduction of oxygen vacancies in the materials, which will provide more physical space for Li + storage, changes the intrinsic property of the sample and leads to the higher specific capacity than theoretical value.…”
Section: Resultsmentioning
confidence: 99%
“…(3)), respectively, along with the decomposition of organic electrolyte and the formation of the solid electrolyte interphase (SEI). , [34] [42][43][44] In the anodic scan, two oxidation peaks at~1.50 and~2.05 V can be attributed to the oxidation of Mn and Co, respectively, corresponding to Eq. (2)-(5).…”
Section: Resultsmentioning
confidence: 99%